Knowledge and Action in Non-Dualistic Vedānta: The Incongruity - K Raina, Simran (Tattva Journal of Philosophy, 2019)
Non-dualistic Vedanta insists on the importance of knowledge rather than action for attaining liberation. Knowledge is regarded as the direct and immediate means of liberation. The cause of the bondage is ignorance (avidyā) and the latter can be removed by knowledge. Non-dualistic Vedānta advocates that the individual is ignorant of the truth that his Self is none other than the Brahman and gets involved in the chain of transmigration. Knowledge of the Self leads to liberation. However, this position leads to a debate between Non-dualistic Vedānta and Mīmāmsā School of thought with reference to understanding whether knowledge itself is a mental action. The objective of the present paper is to examine whether knowledge can be regarded as a mental action.